MENCIPTAKAN WIRAUSAHA DI RUMAH - Hotmaria Tampubolon (JURNAL KELUARGA SEHAT SEJAHTERA, 2014)
ABSTRACT Entrepreneurship is expected to grow in Indonesia, in line with the ratio of the total population by the number of existing businesses, where entrepreneurs in Indonesia is still very low (0.24%) when compared with the number of entrepreneurs in Singapore about 7%, India 10% and China 10%. The Government strongly encourages the growth of the number of entrepreneurs in Indonesia, because the increase in the number of entrepreneurs will support the economy and increase employment opportunities that reduce unemployment. Policies and programs to accelerate growth in the number of entrepreneurs from various parties, both private and government agencies involved to encourage the entrepreneurial spirit, which can be started from around the house. With the knowledge, skills and practical experience gained through formal and informal channels, someone is very likely to open a business / entrepreneurship at home. Business / entrepreneur in the home is a business activity carried on in homes since the process to marketing. Kata Kunci : Wirausaha.